Экспериментальное исследование элементов корпусов БТР-80 - Гриценко, Геннадий Дмитриевич; Малакей, Андрей Николаевич; Ткачук, Николай Анатольевич (Национальный технический университет "Харьковский политехнический институт", 2006)
Запропоновано технологію розрахунково-експериментальних досліджень елементів корпусів бронетранспортерів. Обгрунтовані параметри розрахункових моделей. Наведені результати досліджень тестових зразків пластин методом голографічної інтерферометрії.

Technology of computational-experimental researches of corps elements of the armoured troop-carriers is offered. The parameters of computational models are grounded. The results of researches of plates test models by the method of holographic interferometry are given.
Keywords: бронетранспортеры; напряженно-деформированное состояние; конечно-элементная модель; бронекорпуса; обработка; сварные образцы